DESIGN AND CONSTRUCTION OF DIGITAL LASER COMBUSTION INSTRUMENT AND SYNTHESIS OF SILVER NANOPARTICLES (AgNPs) - Shivasagar, K R; Harisha, K S; Swathi, K R; Srikanth, N; Sangappa, Y; Madhukumar, R; Manjunatha, H V (MATTER: International Journal of Science and Technology, 2019)
The present work focus to the design and development of digital combustion instrument for synthesis of nanoparticles by laser combustion method. This instrument is capable of controlling the synthesis just by giving digital i/p (input), we can prepare more sample of linearly varying different physical variables with digital accuracy and it consume less time and power, sample prepared with this instrument can also be further characterized by Transmission Electron Microscope (TEM). The shape evolution and size of the formed silver nanoparticles was studied using transmission electron microscope. The captured images shown the formed particle were spherical in shape, surface morphology, and diameter in the AgNPs its range from 10 to 20 nm.